The Nutritional Efficacy of Chlorella Supplementation Depends on the Individual Gut Environment: A Randomised Control Study - Nishimoto, Yuichiro; Nomaguchi, Tatsuhiro; Mori, Yuka; Ito, Masaki; Nakamura, Yuya; Fujishima, Masaki; Murakami, Shinnosuke; Yamada, Takuji; Fukuda, Shinji (Frontiers in Nutrition, 2021)
Recent studies have accumulated evidence that the intestinal environment is strongly correlated with host diet, which influences host health. A number of dietary products whose mechanisms of influence operate via the gut microbiota have been revealed, but they are still limited. Here, we investigated the dietary influence of Chlorella, a green alga commercially available as a dietary supplement. A randomized, double-blind, placebo-controlled crossover trial including 40 Japanese participants with constipation was performed and followed by integrated analysis of the gut microbiome, gut metabolome and blood parameters. We revealed that the consumption of Chlorella increased the level of several dicarboxylic acids in faeces. Furthermore, the analysis showed that individuals with low concentrations of faecal propionate increased its concentration by Chlorella intake. In addition, increasing of blood folate levels were negatively correlated with defecation frequency at baseline. Our study suggested that the effect of Chlorella consumption varies by individuals depending on their intestinal environment, which illustrates the importance of stratified dietary management based on the intestinal environment in individuals.